2017
DOI: 10.1037/drm0000059
|View full text |Cite
|
Sign up to set email alerts
|

Reality testing and the mnemonic induction of lucid dreams: Findings from the national Australian lucid dream induction study.

Abstract: Lucid dreaming is a learnable skill and has a wide range of potential applications. However, research in this area has been limited by a lack of effective and reliable lucid dream induction techniques. The present study provides a thorough investigation into 3 of the most promising cognitive lucid dream induction techniques-reality testing, wake back to bed (WBTB), and the mnemonic induction of lucid dreams (MILD) technique. A sample of 169 Australian participants completed a pretest questionnaire, provided ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 41 publications
5
43
2
3
Order By: Relevance
“…Subsequent studies showed that combining MILD with a longer period of wakefulness of either 30 to 60 minutes late in the sleep cycle was associated with even higher increases in lucid dream frequency in the ensuing sleep period [ 18 ]. Consistent with these findings, a recent study found that participants who practiced a combination of MILD and sleep interruption nightly for two weeks demonstrated increased lucid dreaming frequency [ 19 ].…”
Section: Introductionmentioning
confidence: 60%
“…Subsequent studies showed that combining MILD with a longer period of wakefulness of either 30 to 60 minutes late in the sleep cycle was associated with even higher increases in lucid dream frequency in the ensuing sleep period [ 18 ]. Consistent with these findings, a recent study found that participants who practiced a combination of MILD and sleep interruption nightly for two weeks demonstrated increased lucid dreaming frequency [ 19 ].…”
Section: Introductionmentioning
confidence: 60%
“…Recently, a combination of daily reality checks, WBTB, and MILD was associated with LD recall in 53% of participants over the course of one week (Aspy, Delfabbro, Proeve, & Mohr, 2017). Appel (2013) found that WBTB utilizing a 20-30 minute wake interval and cue stimulation in subsequent REM sleep induced lucid dreams in 2 of 5 participants on the second experimental night.…”
Section: Introductionmentioning
confidence: 99%
“…In Studien ohne EEG und EOG werden die Maßeinheiten "Traum Zähler" und "Luzide Traum Frequenzen" benutzt. Ersteres beschreibt die Anzahl der subjektiv erlebten luziden Träume in einer festgelegten Zeit und letzteres die Anzahl an Nächten, in denen mindestens ein luzider Traum erlebt wurde (12).…”
Section: Review Luzides Träumenunclassified
“…Verschiedene Studien weisen darauf hin, dass grundlegende Techniken existieren, mit deren Hilfe das Klarträumen erlernt werden kann (5,12). Zum Erlernen des Klarträumens sind zwei Strategien hilfreich: das Schulen der Traumerinnerung und das Hinterfragen der Realität im Wachzustand.…”
Section: Grundlagen Zum Erlernen Von Klarträumenunclassified